146k views
1 vote
Solve for x: -4√3x-2 +6=22
Show your work.

User Sagine
by
6.1k points

2 Answers

3 votes

The solution depends on the argument of the square root. Please be more precise and less ambiguous when writing your questions.

You could either mean:


-4√(3)x-2+6=22,\quad -4√(3x)-2+6=22,\quad -4√(3x-2)+6=22

In the first case, we have


-4√(3)x-2+6=22 \iff -4√(3)x= 18 \iff x = -(18)/(4√(3))

In the second case, we have


-4√(3x)-2+6=22 \iff √(3x)=-(9)/(2)

which has no solution, because a square root can't be negative

In the third case, we have


-4√(3x-2)+6=22 \iff -4√(3x-2)=16 \iff √(3x-2)=-4

which again has no solution, for the same reason.

User Dustin Martin
by
5.6k points
3 votes


- 4 √(3) x - 2 + 6 = 22 \\ - 4 √(3)x + 4 = 22 \\ - 4 √(3)x = 18 \\ x = (18)/( - 4 √(3) ) = ( - 18 √(3) )/(12) = ( - 3 √(3) )/(2) = - 1.5 √(3)

HOPE THIS WILL HELP YOU

User Lunchbox
by
6.0k points